Philosophical reflections on the concepts of law and justice - Fernández Fernández, César Anibal (2018)
In the present article some philosophical reflections are made on the concepts of "Right" and "Justice", pretending their analysis from the legal axiology, region of knowledge from which we will focus the topic to be treated. In its development, the Theory of Justice by John Ralws is briefly mentioned, as well as the Axiological Relativism of Scandinavian Social Empiricism by Alf Ross.